Pengaruh Persepsi Harga, Citra Merek Dan Electronic Word Of Mouth (E- WOM) Terhadap Minat Beli Aplikasi musik Spotify Premium - Laili Maghfiroh; Siti Aminah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The presence of music applications is an influence on people's lifestyles, especially the Millennial generation. The lifestyle of people who are influenced by the existence of the internetand current trends and the continued development of devices that increasingly provide convenience in supporting online activities, causing a shift in music listening habits from CD / radio to online music streaming, this shift causes a new trend, namely free topaid listening behavior. This study aims to determine the effect of price perception, Brand Image and E-WOM on Buying Interest in Spotify Premium Music Application Services. This research is included in the type ofquantitative research with the method of collecting data in the form of questionnaires. The sample in this study amounted to 80 respondents The sampling technique used was non-probability sampling with the purposive sampling method. Data are obtained by distributing questionnaires. The data analysis method uses Partial Least Square (PLS) analysis with the help of the Smart PLS 3.0 program, From the results of the study shows that Price Perception, Brand Image and E-WOM have a positive and significant effect on the Buying Interest of Spotify Premium Music Application Services. This is inline with the hypothesis, itcan be said to be significant (positive).